Apa yang Diperlukan dan Disiapkan untuk Menjadi Seorang Guru Matematika? - Yoppy Wahyu Purnomo; Irfan Wahyu Prananto (Jurnal Inovasi Pendidikan Dasar, 2020)
The mathematics teacher profession has become a challenging and interesting profession in the era of technological advancement and global competition. The fact that mathematics is difficult is not able to stop interested (students) to become mathematics teachers. This is a basic asset that they have seen the opportunities behind challenges. This article aims to provide an overview of prospective mathematics teacher candidates regarding the opportunities, hopes, demands, and challenges of becoming a mathematics teacher. To accommodate these objectives, the article is divided into three main sections related to the question: Why choose a mathematics education study program? What does it take to be a math teacher? What needs to be prepared to become a mathematics teacher? These three questions are answered in their respective sections in the hope that they can give an idea of ??what needs to be done, what has been done, and how the students of mathematics teacher candidates follow the lectures.